Prophetic preaching in the socio-economic and socio-political crisis of Zimbabwe - Fenga, Vincent F.; Wepener, Cas (Verbum et ecclesia, 2018)
In Zimbabwe, there are different preachers who have great names, but when it comes to prophetic preaching they lag behind as compared to South Africa, which has great preachers in prophetic preaching like Desmond Tutu. In this era, however, we are challenged with a situation of socio-economic and socio-political crisis: the enormous poverty among approximately 95% of the population. This article discusses the circumstances for prophetic preaching in the contemporary context of Zimbabwe, which are a clear understanding of the poverty position and cohesion of the church with the poor, a good understanding of the image of prophetic preaching as a specific type of preaching that encompasses the four elements of preaching: the preacher, as well as the congregation (hearers), the sermon and the Holy Spirit for prophetic preaching. Interdisciplinary and intradisciplinary implications: This article discusses the circumstances for prophetic preaching in the context of Zimbabwe, which are a clear understanding of the poverty position and cohesion of the church with the poor. In our analysis of prophetic preaching in Zimbabwe, the emphasis is put on prophecy, healing, deliverance and prosperity. This article argues that prophetic preaching is approaching the biblical text with a view to interpret it as preaching in a context of poverty. It should be done from the perspective of the poor, therefore in terms of their need for justice and righteousness.